Identificação de possíveis intervenções voltadas para a redução de riscos de inundações na bacia hidrográfica do rio Palmital localizada na área do município de Pinhais/PR - Pinheiro, Andrea Magnuski (2014)
The River Basin Palmital plays an important role in the availability of water resources for the local and neighboring regions society. Understanding the importance of water resources and all the dynamics involved , this study aims to identify possible interventions to contain floods in River Basin Palmital within the limits of the municipality of Pinhais - PR . Raising data for improved environmental planning area, providing information which would facilitate compliance with the Master Plan of the City of Pinhais , county to which the proposed research interventions to reduce flood risks. To develop the study was organized a database of environmental data from the catchment area of the river Palmital , integrating the altimetry , and gauged precipitation data , identifying the historical flood data that generated mainly socio- economic losses . First, there was the study of the physical and geomorphological characteristics of the basin generating thematic maps using ArcView software . From the rainfall and runoff data a study of quota river flow Palmital with the highest precipitation was performed by relating these data with the floods that occurred days . The result identified as flood losses were incurred for the years 2003 , 2009, 2010 and 2011 . After making this identification the map with the coordinates of historical floods was prepared to know the areas that are most susceptible to this extreme hydrological event and thus propose that the area is considered a risk of flooding . Through the study it was found that the most affected areas are the mouth and the next right bank Palmital , an area of consolidated urbanization . It is proposed for these areas , such as non- structural measure , an early warning system for floods along with Civil Defence and environmental education for the public awareness of the risks to which it is subject , and as a structural measure the construction of detention ponds / retention as a linear park , also using them as wetland systems for the treatment of river water in times of drought , as this river is as committed and framed as class 3 by CONAMA Resolution No. 430 quality. For future research it is recommended that a study may indicate interference in the headwaters , because these could help more significantly in preventing floods , and could result in lower in relation to the interventions of structural measures costs.